Sprouty4 is epigenetically upregulated in human colorectal cancer. Issue 1 (31st December 2023) - Stuckel, Alexei J.; Zeng, Shuai; Lyu, Zhen; Zhang, Wei; Zhang, Xu; Dougherty, Urszula; Mustafi, Reba; Khare, Tripti; Zhang, Qiong; Joshi, Trupti; Bissonnette, Marc; Khare, Sharad
ABSTRACT: Sprouty4 (SPRY4) has been frequently reported as a tumor suppressor and is therefore downregulated in various cancers. For the first time, we report that SPRY4 is epigenetically upregulated in colorectal cancer (CRC). In this study, we explored DNA methylation and hydroxymethylation levels of SPRY4 in CRC cells and patient samples and correlated these findings with mRNA and protein expression levels. Three loci within the promoter region of SPRY4 were evaluated for 5mC levels in CRC using the combined bisulfite restriction analysis. In addition, hydroxymethylation levels within SPRY4 were measured in CRC patients. Lastly, DNA methylation and mRNA expression data were extracted from CRC patients in multiple high-throughput data repositories like Gene Expression Omnibus and The Cancer Genome Atlas. Combined in vitro and in silico analysis of promoter methylation levels of SPRY4 clearly demonstrates that the distal promoter region undergoes hypomethylation in CRC patients and is associated with increased expression. Moreover, a decrease in gene body hydroxymethylation and an increase in gene body methylation within the coding region of SPRY4 were found in CRC patients and correlated with increased expression. SPRY4 is epigenetically upregulated in CRC by promoter hypomethylation and hypermethylation within the gene body that warrants future investigation of atypical roles of this established tumor suppressor. Key policy highlights: SPRY4 gene expression is increased in colorectal cancer The SPRY4 promoter loses DNA methylation, and the gene body gains DNA methylation in colorectal cancer The gene body of SPRY4 loses DNA hydroxymethylation